Understanding the effects of opioids vs non-opioids in the treatment of neonatal abstinence syndrome, an in vitro model - Sithisarn, Thitinart; Legan, Sandra J.; Westgate, Philip M.; Bada, Henrietta S.; Wilson, Melinda E. (Frontiers in Pediatrics, 2022)
Neonatal abstinence syndrome (NAS) refers to cadre of withdrawal manifestations in infants born to mothers who used illicit and licit substances during pregnancy. The increasing prevalence of NAS has been largely due to the maternal use of opioids during pregnancy. NAS contributes to increased morbidity and long-term disability in surviving infants. Clinically, oral opioid therapies for opioid exposure have been a standard treatment with morphine (MO) being the most commonly used medication. Recently, a non-opioid agent, clonidine (CD) has also been used with potentially favorable short- and long-term outcomes in infants. However, data regarding the cellular and molecular effects of these treatments on the developing brain is still lacking due to a lack of a reliable animal model that targets the neonatal brain. To address this gap in knowledge we determined the effects of MO or CD on the cell death of neonatal cortical explant cultures that were exposed to oxycodone (OXY) in utero. Sprague Dawley rats were randomized and implanted with programmable infusion pumps before mating to receive either the OXY (dose increasing from 1.21-1.90 mg/kg/day to a maximum dose of 2.86-3.49 mg/kg/day) or normal saline (NS) throughout pregnancy and until one week after delivery. Male and female rat pups were sacrificed on postnatal day 4, and the prefrontal cortex (PFC) and hippocampus (HC) were dissected and treated with MO (0.10-1.00 µM) or CD (1.20-120.00 µM) in culture media. After 5 days of treatment the explants were labeled with propidium iodide to detect cell death. Dead cells were analyzed and counted under fluorescence microscopy. In explants from the PFC, cell death was greater in those prenatally exposed to OXY and postnatally treated with MO (OXY/MO) (736 .8 ± 76.5) compared to OXY/CD (620 .9 ± 75.0; p = 0.005). In the HC explants, mean cell death counts were not significantly different between groups regardless of prenatal exposure or postnatal treatment (p = 0.19). The PFC is vital in controlling higher-order executive functions such as behavioral flexibility, learning and working memory. Therefore, our finding is consistent with executive function problems in children with prenatal opioid exposure.